Internal and External Resources Relied on by Established Twelve Step Fellowship Members for Their Recoveries. (2nd January 2023) - Galanter, Marc; White, William L.; Hunter, Brooke
ABSTRACT: Background: The Twelve Steps described by Narcotics Anonymous (NA) and Alcoholics Anonymous denote key aspects of how members can achieve abstinence from alcohol and other drugs. However, there are limited empirical findings on what long-term members rely on to support their ongoing recovery. Method: In order to clarify the members' reliance on those latter resources, we surveyed 2, 293 long-term NA members through the internet on items they rely on for their recovery. They scored nine NA-related resources (e.g., their sponsor) and three non-NA institutional ones (e.g., a professional therapist). Results: Three factors accounted for 53.6% of the variance in the respondents' scores of the 12 items. We labeled them, with the percent of variance accorded, as NA-based social (24.9%) support, spiritual (17.8%) support, and outside professional (10.9%) help. While NA-based resources ranked highest, outside resources (a house of worship, a therapist, or medications for psychological distress) were scored by 75.4% of the respondents. Analysis by subgroups of respondents reflected the diversity of resources members draw on. The use of internet-based meetings during the COVID-19 period reflected the resilience of the NA format. Conclusion: Members of Twelve Step programs can be studied to shed light on options that they rely on for support for their ongoing recovery, both within the fellowships and outside them. Long-term members can apparently rely on resources inside the fellowship and simultaneously on professional ones, as well. These findings can be helpful for researchers in considering mechanisms that underlie long-term Twelve Step-related recovery and for clinicians in employing both these fellowships and outside resources as adjuncts to their professional care.